Beta 1, 3/1, 6-glucan and vitamin C immunostimulate the non-specific immune response of white shrimp (Litopenaeus vannamei). (October 2016) - Wu, Yu-Sheng; Liau, Shu-Yu; Huang, Cheng-Ting; Nan, Fan-Hua
Abstract: This study mainly evaluated the effects of orally administered beta 1, 3/1, 6-glucan and vitamin C on the nonspecific immune responses of white shrimp ( Litopenaeus vannamei ). In this study, we found that the white shrimp oral administration with 1 g/kg of beta 1, 3/1, 6-glucan effectively enhanced O2 − production and phenoloxidase and superoxide dismutase activity. Shrimp were oral administration with 0.2 g/kg of vitamin C presented beneficial nonspecific immune responses and enzyme activity and also observed in the beta 1, 3/1, 6-glucan treatment groups. Consequently, we compared the alterations in the immune activity between the beta 1, 3/1, 6-glucan and vitamin C groups and the evidence illustrated that combination of beta 1, 3/1, 6-glucan and vitamin C presented an additive effect on inducing the nonspecific immune responses of white shrimp. Highlights: Induction of O2 − production, PO and SOD activity was observed in the beta 1, 3/1, 6-glucan and vitamin C treatment. Supplement of vitamin C reduce the GOT and GPT activity. Combination of beta 1, 3/1, 6-glucan and vitamin C has an additive effect on inducing the nonspecific immune response.